Morphological signs of the effectiveness of application sorbent in the treatment of purulent wounds (experimental study) - Bilyayeva, O. O.; Dyadyk, O. O.; Zaritsʹka, V. I.; Kryzhevskyi, Ye. Ye. (Морфологія / Morphologia / Morfologìâ, 2021)
Objective. To prove experimentally the effectiveness of a new generation of application sorbent by studying the morphological changes during the wound process. Methods. Depending on the drug used to treat purulent wounds, we divided the animals into three groups. In the main group (group I) the study was performed on 20 rats, they used an application sorbent, which includes aerosil with immobilization on its matrix ornidazole (Patent of Ukraine for utility model № 115228). The comparison group (group II) consisted of 10 rats, which used the known sorbent "Gentaxan", which includes: gentamicin sulfate, L-tryptophan and zinc sulfate. The comparison group (group III) was 10 rats. In this group for the treatment of purulent wounds used 10% sodium chloride solution, followed by a transition to ointment "Levomekol", which includes chloramphenicol and methyluracil. Results. The results of the study show that in the main group already on the seventh day in comparison with the comparison groups was found granulation tissue with a large number of newly formed vessels of the microcirculatory tract and pronounced proliferation of fibroblasts, indicating acceleration of wound healing. In the comparison groups, the regeneration process was slower. Conclusion. Pathomorphological examination revealed that drugs with sorption properties contribute to a faster reduction of edema and inflammation, and treatment with application sorbent used in the main group, significantly accelerates the processes of connective tissue repair and wound epithelization, ie accelerates wound healing processes with comparison groups.